Totally laparoscopic treatment of intestinal tuberculosis complicated with bowel perforation: The first case report in worldwide literature with a brief review - Di Buono, Giuseppe; Vella, Roberta; Amato, Giuseppe; Romano, Giorgio; Rodolico, Vito; Saverino, Marta; De Lisi, Giovanni; Romano, Giorgio; Buscemi, Salvatore; Agrusa, Antonino (Frontiers in Surgery, 2022)
Introduction Bowel perforation is a relatively rare presentation of abdominal tuberculosis, whose diagnosis is challenging but fundamental to minimize morbidity and mortality. Laparoscopy is considered an effective modality for diagnosis, but its role in surgical treatment is still not established. We reported the first worldwide case of totally laparoscopic treatment of intestinal tuberculosis complicated with bowel perforation. Case presentation A 30-year-old man with a history of weight loss, preceded by 2 years of nonproductive cough, was admitted to the Infectious Disease Department with a presumed diagnosis of tuberculosis. A microbiological culture test confirmed the diagnosis, and the patient undertook quadruple antituberculous therapy. During hospitalization, he presented sudden abdominal pain, fever, and vomit. An abdominal CT scan showed small bowel perforation with granulomatous reaction. Laparoscopy was performed and revealed a 2 cm perforation on the medium ileum. Small bowel resection and totally intracorporeal side-to-side anastomosis were performed. No complication occurred until a clinical follow-up of 2 months. Conclusion In consideration of the increasing incidence of intestinal TB in both underdeveloped and Western countries, the diagnosis of this pathology should be taken into account in high-risk patients. Probably, the diagnostic challenges and emergency settings of intestinal TB with perforation and peritonitis, together with the lack of standardized guidelines regarding surgical management, make the use of laparoscopy apparently arduous, but the known advantages of laparoscopy and its technical feasibility should make it a conceivable option for the treatment of complicated cases.